2020
DOI: 10.3389/fbioe.2019.00467
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Trends in the Trabecular Micro-Architecture of the Medial Clavicle: Is It of Use in Forensic Science?

Abstract: The mechanical and structural properties of bone are known to change significantly with age. Within forensic and archaeological investigations, the medial end of the clavicle is typically used for estimating the age-at-death of an unknown individual. Although, this region of the skeleton is of interest to forensic and clinical domains, alterations beyond the macro-scale have not been fully explored. For this study, non-destructive micro-computed tomography (µ-CT) was employed to characterize structural alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
1
11
0
1
Order By: Relevance
“…Bone histology applied in age estimation through the quantification of microscopic features is feasible due to cortical and trabecular remodeling occurring over time reflecting the chronological age of an individual [7][8][9]. Despite several microscopic methodological drawbacks such as specialized equipment and training [10], many researchers have been using histomorphometric assessment of bones and teeth for human identification purposes in both forensic anthropology and bio-archaeology research since 1965 [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Bone histology applied in age estimation through the quantification of microscopic features is feasible due to cortical and trabecular remodeling occurring over time reflecting the chronological age of an individual [7][8][9]. Despite several microscopic methodological drawbacks such as specialized equipment and training [10], many researchers have been using histomorphometric assessment of bones and teeth for human identification purposes in both forensic anthropology and bio-archaeology research since 1965 [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary results fall within the standard error reported by macroscopic methods [38], with the possibility of being used for highly fragmented or taphonomically affected human costal elements. Moreover, a subset of 24 individuals from the Albanian sample was recently tested for age-estimation based on observed changes on the trabecular bone of the medial end of the clavicle through µ-CT [39]. The results showed that there was a different trend in qualitative trabecular changes before and after 23 to 25 years of age and volumetric tissue mineral density and trabecular number decreased throughout the age ranges span.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the age-at-death estimation, morphometric properties of the trabecular micro-architecture of bones belonging to several different anatomical districts have been investigated demonstrating that several quantitative parameters change with age. In fact, for instance, the thickness of the trabeculae in the iliac and pubic bone [52,53] and bone volume, mineral density, and the number of trabeculae of the medial clavicle [54] increased with age while the trabecular bone volume in the posterior part of the auricular surface decreased with age [55] (Fig. 3B).…”
Section: Anthropological Investigationsmentioning
confidence: 95%